Abordagens para análise de n-nitrosaminas em medicamentos utilizando DPX-LC-MS e DART-MS - Batista Junior, Almir Custodio (2023)
N-Nitrosamines (NAs) are molecules characterized by a deprotonated amine group linked to a nitroso group, usually formed through the reaction of secondary or tertiary amines with nitrosating agents. NAs are commonly found as impurities in various products, such as processed foods and cosmetics. These molecules are the subject of study due to their potential mutagenic and carcinogenic properties. In 2018, NAs were discovered in medicines containing the active ingredient valsartan. In sartan medicines, the occurrence of NAs was initially linked to the synthesis of the active pharmaceutical ingredient (API), as the reaction medium may contain precursor amines for NAs, as well as a nitrosating agent. Through more in-depth studies, it has been confirmed that the degradation of the API or its interaction with the packaging material could lead to the formation of NAs. These discoveries prompted global regulatory agencies to establish guiding principles regarding the presence and maximum allowable concentrations of these molecules in such medicines. Aiming to assess the content of NAs in medicines, efficient and sensitive analytical methods have been developed. The challenge in analyzing NAs in medicines lies in the low concentration of these analytes, as they are found in this matrix in the order of ng of N-nitrosamine per mg of the medicines. The literature presents various chromatographic methods coupled with mass spectrometry (MS) applied in such analyses. Both liquid chromatography (LC) and gas chromatography (GC) techniques provide sensitive and selective methods for the analysis of NAs in medicines. However, LC methods have advantages over GC as it allows the analysis of thermally unstable and non-volatile compounds. Due to the presence of the API in the sample and the low concentration of these impurities, the determination of NAs can be compromised by various factors, such as matrix effects, carryover effects, and the compromise and contamination of the LC-MS system. Thus, the sample preparation step proves to be important, aiming at the extraction, purification, and pre-concentration of NAs. Additionally, advances in mass spectrometry have led to the development of ambient ionization techniques designed to analyze samples that are either unprocessed or minimally modified in their native environment. These techniques enable the analysis of samples in situ, often in a non-destructive manner. Another important factor currently is the adaptation of analysis protocols with sustainable principles advocated by green chemistry, which aim to reduce the use of solvents and samples, minimize risks, decrease energy consumption, and reduce waste generation. Therefore, the present study introduces new approaches to the analysis of NAs in medicines that have not yet been explored in the literature. Chapter I demonstrates the use of a miniaturized sample preparation technique for the separation and pre-concentration of NAs in medicines followed by LC-MS analysis. Conversely, Chapter II presents the application of an ambient ionization technique coupled with mass spectrometry for the assessment and quantification of NAs in medicines.